Optimal financing for growth firms - Langberg, Nisan (Journal of Financial Intermediation, 2008)
We analyze the optimal contract to finance the series of investments of a growing firm. The analysis is based on the need to repeatedly raise funds when informed insiders can expropriate outside investors. The optimal contract can be implemented by a sequence of one-period debt contracts and equity ownership by outsiders. Debt is optimal, as it reduces the expected cost of auditing, while partial equity ownership by insiders is optimal, as it mitigates the need for auditing in the presence of valuable growth opportunities. The model yields time-series implications regarding capital structure, investment and its fraction financed externally, and profitability.